Final answer:
To solve the equation x - 2/3 = 6 1/3, subtract 2/3 from both sides and convert 6 1/3 into an improper fraction. The solution is x = 17/3.
Step-by-step explanation:
To solve the equation x - 2/3 = 6 1/3, we need to isolate the variable x. First, we'll subtract 2/3 from both sides of the equation:
x - 2/3 - 2/3 = 6 1/3 - 2/3
Simplifying both sides, we get:
x = 6 1/3 - 2/3
Now, we'll convert 6 1/3 into an improper fraction:
6 1/3 = (3 * 6) + 1 = 19/3
Thus, the solution to the equation is:
x = 19/3 - 2/3 = 17/3